(untitled) (International Journal of Engineering and Computer Science, 2017)
UNI-BOOKS‖ is the web service for the students of particular university where students can sell or buy old books directly to or from other students. The main objective of the project is to create an online book store that allows users to search and purchase old books online based on title, author and subject. The chosen books are displayed in a tabular format and the user can order their books online through cash on delivery payment. Using this Website the user can buy a book online instead of going out to a book store and wasting time.